Biopesticide Consumption in India: Insights into the Current Trends - Chakraborty, Nilanjan; Mitra, Rusha; Pal, Somrhita; Ganguly, Retwika; Acharya, Krishnendu; Minkina, Tatiana; Sarkar, Anik; Keswani, Chetan (Agriculture (Basel), 2023)
Biopesticides are formulations derived from naturally occurring compounds that manage pests through non-toxic and environmentally favorable means. Being living organisms (natural enemies) or products, biopesticides represent less of a risk to the environment and to human health. Biopesticides, classified into three broad classes, are increasingly used in pest control, and include semiochemicals, plant-incorporated protectants (PIPs), and compounds derived from plants and microorganisms. Because of their advantages for the environment, target-specificity, efficacy, biodegradability, and applicability in integrated pest management (IPM) programs, biopesticides are gaining interest. Although biopesticides have seen significant advances in market penetration, they still make up a relatively small fraction of pest management solutions. Over 3000 tons are produced globally per annum, and this number is rising rapidly. In India, biopesticides account for just 4.2% of the country’s total pesticide market. Although the government has promoted the use of biopesticides by including them in several agricultural programs, biopesticides face numerous difficulties at a local level, but are predicted to expand at an astonishing 10% yearly pace. Under the Insecticides Act 1968, the Ministry of Agriculture in India controls the use of pesticides. Among the major biopesticides produced and used in India are Trichoderma, Bacillus thuringiensis, nuclear polyhedrosis virus, and neem-based pesticides.